VLNDEF project for Geodetic Infrastructure definition of northern Vicotoria Land, Antarctica - CAPRA, Alessandro; M. Dubbini; A. Galeandro; L. Gusella; A. Zanutta; G. Casula; M. Negusini; L. Vittuari; P. Sarti; F. Mancini; S. Gandolfi; S. Montaguti; et al. (SPRINGER, 2008)
Scientific investigations in Antarctica are, for many different reasons, a challenging and fascinating task. Measurements, observations and field operations must be carefully planned well in advance and the capacity of successfully meeting the goals of a scientific project is often related to the capacity of forecasting and anticipating the many different potential mishaps. In order to do that, experience and logistic support are crucial. On the scientific side, the team must be aware of its tasks and be prepared to carry out observations in a hostile environment: both technology and human resources have to be suitably selected, prepared, tested and trained. On the logistic side, nations, institutions and any other organisation involved in the expeditions must ensure the proper amount of competence and practical support.The history of modern Italian Antarctic expeditions dates back to the middle 80’s when the first infrastructures of “Mario Zucchelli Station”, formerly Terra Nova Bay Station, were settled at Terra Nova Bay, Northern Victoria Land. Only a few years later, the first geodetic infrastructures were planned and built. Italian geodetic facilities and activities were, ever since, being constantly maintained and developed. Nowadays, the most remarkable geodetic infrastructures are the permanent Global Positioning System (GPS) station (TNB1) installed at Mario Zucchelli and the GPS geodetic network Victoria Land Network for DEFormation control (VLNDEF) entirely deployed on an area extending between 71° S and 76° S and 160° E and 170° E.These facilities do not only allow carrying out utmost geodetic investigations but also posses interesting capacities on the international multidisciplinary scientific scenario.In order to fully exploit their potentiality, management and maintenance of the infrastructure are crucial; nevertheless, in order to perform high quality scientific research, these abilities must be coupled with the knowledge concerning a proper use and a correct processing of the information that ...